2013
DOI: 10.1002/hon.2094
|View full text |Cite
|
Sign up to set email alerts
|

The combined expression of VPREB3 and ID3 represents a new helpful tool for the routine diagnosis of mature aggressive B‐cell lymphomas

Abstract: Genomic studies, such as gene expression profiling and next-generation sequencing studies, have provided new insights into the phenotypic characteristics and pathogenesis of mature aggressive B-cell lymphomas. In particular, mutations in the transcription factors ID3 and TCF3, leading to overexpression of B-cell receptor components such as VPREB3, have been shown to be specific for Burkitt lymphoma (BL) and play an important tumourigenic role by mediating the activation of the pro-survival phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The expression of Vpreb3/ pre B-lymphocyte protein 3 was found to be decreased in MMP-9 −/− mice compared to WT mice in both control and DSS conditions. Vpreb3 is expressed during B-cell differentiation in subsets of mature B lymphocytes and is linked to formation of B-cell lymphomas31. Many genes ( n =249) were found to be uniquely expressed by MMP-9 −/− mice after DSS administration.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Vpreb3/ pre B-lymphocyte protein 3 was found to be decreased in MMP-9 −/− mice compared to WT mice in both control and DSS conditions. Vpreb3 is expressed during B-cell differentiation in subsets of mature B lymphocytes and is linked to formation of B-cell lymphomas31. Many genes ( n =249) were found to be uniquely expressed by MMP-9 −/− mice after DSS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found CCN2 upregulated in B-ALL compared to T-ALL ( Table 3 ). It is worth highlighting that VPREB3 is a B-cell receptor component [100], which explains its upregulation in B-ALL compared to T-ALL ( Table 3 ). Increased gene expression of this gene can activate the pro-survival phosphatidylinositol-3-OH kinase pathway [100].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth highlighting that VPREB3 is a B-cell receptor component [100], which explains its upregulation in B-ALL compared to T-ALL ( Table 3 ). Increased gene expression of this gene can activate the pro-survival phosphatidylinositol-3-OH kinase pathway [100]. Recently, another study also analyzed molecular differences between B-ALL and T-ALL and found VPREB3 as a methylation and expression signature gene [101].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ID1 and ID3 coexpression was correlated with a poor clinical outcome in patients with locally advanced non-small cell lung cancer treated with definitive chemoradiotherapy [ 39 ]. The combined expression of VPREB3 and ID3 was used to develop a new helpful tool for the routine diagnosis of mature aggressive B-cell lymphomas [ 40 ]. All these results suggested the prognostic value of ID3 expression in diverse human cancers.…”
Section: Discussionmentioning
confidence: 99%